Novel Disubstituted Calix[4]arenes Containing Chromogenic Groups on the Lower Rim: Synthesis, Structural Identification, and Absorption Properties - Şener, Nesrin; Erişkin, Selinay; Gür, Mahmut; Şener, İzzet (Wiley, 2018)
5,11,17,23‐Tetra‐tert‐butyl‐25,26,27,28‐tetrahydroxycalix[4]arene and 25,26,27,28‐tetrahydroxycalix[4]arene were synthesized based on previous literature. Firstly, several azo dyes were synthesized, and then, these dyestuffs were chlorinated through reaction with thionyl chloride. Secondly, the azo compounds bonded with methylene chloride and reacted with 25,26,27,28‐tetrahydroxycalix[4]arene, and then, six novel disazocalix[4]arene derivatives 4(a–f) were achieved. Their structures were characterized as Fourier transform infrared, 1H‐NMR, and elemental analysis. In this study, we investigated the solvatochromic properties of the compounds and the acid–base effect on their ultraviolet–visible absorption by using six solvents.
Keywords: synthesis; dimethyl sulfoxide; proton nuclear magnetic resonance; Article; tautomer; azo dye; heterocyclic amine; chemical bond; infrared spectroscopy; methanol; chlorination; chloroform; pH; elemental analysis; dichloromethane; n,n dimethylformamide; unclassified drug; acetonitrile; chromogenic substrate; acetic acid; ultraviolet spectrophotometry; chemical structure; calixarene; disazocalix[4]arene derivative; 3. Good health